A novel compound heterozygous mutation of COL6A3 in Chinese patients with isolated cervical dystonia - Wu, Rui; Dou, Weikang; Zhou, Huimin; Shi, Ming (Frontiers in Neurology, 2023)
Background The etiology and pathogenesis of idiopathic dystonia remain obscure. Recent studies revealed that compound heterozygous mutations in collagen type VI alpha-3 gene COL6A3 may cause recessive isolated dystonia (DYT)-27. However, whether COL6A3 mutations are associated with Chinese patients with isolated dystonia is not yet reported. Methods In this study, 45 Chinese patients with isolated cervical dystonia were recruited, and their blood DNA samples were subjected to whole-exome sequencing. The potential causal variants of COL6A3 were identified based on the criteria of the American College of Medical Genetics and Genomics and by prediction software. Results Among 45 isolated cervical dystonia patients, 18 patients (10 female patients and eight male patients) were found to have seven potential causal variants in the COL6A3 gene. Among these variants, a compound heterozygous mutation was found in one patient. One allele had a c.1264G>A mutation in exon 4 that resulted in an amino acid substitution of methionine for valine at codon 422 (p.Val422Met) and the other a c.8965+9G>A mutation involving a splicing change in exon 40. In addition, other five missense variants, including c.958G>A (p.Ala320Thr), c.1478T>C (p.Val493Ala), c.1597C>T (p.Arg533Cys), c.1762G>A (p.Asp588Asn), and c.4912G>A (p.Ala1638Thr), were identified as well. Conclusion We identified a novel deleterious compound heterozygous mutation as well as five missense variants in the COL6A3 gene of Chinese patients with cervical dystonia. These findings may expand the spectrum of the COL6A3 genotype in isolated dystonia.